Analisis Ekologi Pada Cerpen Mematungku Di Kaki Bukit Ini Karya Fina Aryadila: Kajian Ekologi Sastra - Enjelita Sormin; Rizka Tri Canty; Ika Febriana (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This study aims to determine the ecology of literary works in the short story Mematungku di Kaki Bukit Ini by Fina Aryadila. This research was conducted with an ecological literary approach. The method used is descriptive by describing the results obtained in the form of words. The results of the study show that this short story contains natural ecology. Natural ecology deals with human interaction with nature, the attitude of human care for nature and how humans act towards nature. In this short story, there are various human traits towards natural conditions, namely sadness, disappointment, indifference and greed. Fina is the main character who feels disappointed, sad and concerned about the condition of the hill which has begun to be damaged by irresponsible, indifferent, and greedy people. This story tells of a hill that was once beautiful, now damaged and converted into a building that will become a long-term asset for humans who are greedy and do not care about the balance of the ecosystem. This short story also tells how the point of view of the character "Aku", namely Fina Aryadila, witnessed the damage to the hill that occurred, such as burning forests, cutting down trees and the hustle and bustle of animals in the forest in saving themselves and moving places.